1981
DOI: 10.2136/sssaj1981.03615995004500040023x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf‐Cutter Ant (Atta cephalotes) Influence on the Morphology of Andepts in Costa Rica

Abstract: Twenty‐seven soil profiles distributed within a 2.5‐ha site were described as Typic Dystrandepts of the Colorado soil series. Leaf‐cutter ant influence was noted in 85% of the pedons. The influence on each profile was estimated, and out of all profiles, 37% had low, 26% medium, and 22% high disturbance. The surface area covered by leaf‐cutter mounds was 38.9% of the study area; only 1% of the aboveground disturbed area was active, however. Leaf‐cutter ants transport material from the AB and B horizons to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 0 publications
0
34
1
Order By: Relevance
“…Bulk density (a function of porosity and organic matter content) of the deposited material was significantly lower than that of the surrounding soil (~0.29-0.53 vs. 1.04 g cm −3 ). Nest building by Atta cephalotes (L.) in a tropical forest resulted in displacement to the surface of an estimated 460 tonnes of subsoil ha −1 over the average colony's lifespan [228]. The authors concluded that leafcutter ants played a major role in soil genesis and development in areas of the New World tropics.…”
Section: Soil Mixing and The Development Of Pores And Voidsmentioning
confidence: 99%
“…Bulk density (a function of porosity and organic matter content) of the deposited material was significantly lower than that of the surrounding soil (~0.29-0.53 vs. 1.04 g cm −3 ). Nest building by Atta cephalotes (L.) in a tropical forest resulted in displacement to the surface of an estimated 460 tonnes of subsoil ha −1 over the average colony's lifespan [228]. The authors concluded that leafcutter ants played a major role in soil genesis and development in areas of the New World tropics.…”
Section: Soil Mixing and The Development Of Pores And Voidsmentioning
confidence: 99%
“…When abundant, ants can modify the soil's physical structure by creating systems of galleries and chambers, influencing soil porosity, aeration, infiltration, and drainage (Lavelle & Spain, 2001). They also change soil texture and other soil properties through the horizontal and vertical transfer of materials of different particle sizes (Alvarado et al, 1981).…”
Section: Soil Macrofauna Densitymentioning
confidence: 99%
“…The soil at the study site is an Andept, derived from aged pyroclastic materials of the IrazuTurrialba volcano complex, and pertains to the Colorado series of Typic Dystrandepts (Alvarado et al, 1981). A typical soil profile has a thin (0 to 6cm) All horizon that has a high organic matter content (ca.…”
Section: Study Sitementioning
confidence: 99%
“…The soil is strongly aggregated, has a rapid infiltration rate (approximately 30 cm hr-1), and a very high water-holding capacity (over 40% by volume at 15 bars of tension) (Russell and Ewel, 1985). Evidence of extensive pedoturbation from leaf-cutter ant activity was present throughout soil profiles (Alvarado et aL, 1981).…”
Section: Study Sitementioning
confidence: 99%